Correlates of Choice of Contraceptive Methods in Pakistan (The Pakistan Development Review, 1995)
Since 1965, contraceptive use rate has been slowly increasing in Pakistan. In 1984-85, contraceptive ever use rate was 11.8 percent and current use rate was 9.1 percent [Government of Pakistan (1986)]. These use rates increased to 20.7 percent and 11.8 percent respectively in 1990-91 [National Institute of Population Studies (1992)]. However, use rates did not increase as expected. Pakistan’s Population Welfare Programme adopted many strategies to increase the use rate of contraceptive methods but although knowledge of contraceptive methods increased to 77.9 percent [National Institute of Population Studies (1992)], use rate remained low. One of the major reasons was inadequate coverage of service delivery. Contraceptive method of choice out of the available variety of contraceptive methods ensures continuation of use and reduces the drop-out rate [Jain (1992)]. The needs and values of individuals change over time and any one method cannot be suitable to an individual’s need all the time. So if more than one method is available, and acceptor can switch over to a more suitable method of choice if the first (or previous) method of choice becomes unacceptable. Also the client’s satisfaction with the method of choice is very important. Clients are best satisfied when they get the methods of their choice from a broad variety or ‘mix’ of contraceptive methods offered on a reliable basis [Jain (1992)].